Smokers’ perception of their health status and health-seeking behaviour: a narrative review - Muhamad Al-Muizz, Ismail; Mohamad Shariff, Nurasikin; Nurumal, Mohd. Said; Abdul Rahman, Razlina; Mohd Mokhtar, Hanida Hani (IIUM Press, 2022)
Smoking has been primarily studied as a public health problem involving mapping continued smoking patterns and interventions designed to decrease smoking prevalence. This paper discusses the available literature on smokers’ perception of their health, health-seeking behaviour, and factors influencing their smoking continuity.Method: Review literature conducted by using databases such as Science Direct, Sage Journals, Wiley, PubMed, and Scopus with the keywords “smoking effect”, “smoking cessation”, “health perception”, “health-seeking behaviour”, “health status”, and “health screening”. Result: Eighteen articles were selected, reviewed, and summarised. These include six qualitative studies, ten quantitative studies, and two randomised control studies. This review showed that many smokers still believe they are healthy despite their unhealthy smoking habits, influencing their health-seeking behaviour. Social acceptance and cultural and religious belief also highly influenced their smoking behaviour. A personalised related factor may influence their decision to cease smoking more than the general advice of adverse effects of smoking. Conclusion: Communication of health risks must align with smokers' perception of health risks which they tend to minimise and ignore. Thus, healthcare providers should develop passion, equipped with ordinary skills and aid while intervening with smokers, which might influence and increase their motivation to quit smoking. Future studies should also look at factors that affect smokers' judgement and decisions when a healthcare provider communicates personal health risks.. Keywords: Smoking Effect; Smoking Cessation; Health Perception; Health-seeking Behaviour; Health Status, Health Screening.